Poly(methyl vinyl ether-alt-maleic acid) and ethyl monoester as building polymers for drug-loadable electrospun nanofibers. Issue 1 (December 2017) - Mira, Amalia; Mateo, C.; Mallavia, Ricardo; Falco, Alberto
Abstract New biomaterials are sought for the development of bioengineered nanostructures. In the present study, electrospun nanofibers have been synthesized by using poly(methyl vinyl ether-alt-maleic acid) and poly(methyl vinyl ether-alt-maleic ethyl monoester) (PMVEMA-Ac and PMVEMA-ES, respectively) as building polymers for the first time. To further functionalize these materials, nanofibers of PMVEMA-Ac and PMVEMA-ES containing a conjugated polyelectrolyte (HTMA-PFP, blue emitter, and HTMA-PFNT, red emitter) were achieved with both forms maintaining a high solid state fluorescence yield without altered morphology. Also, 5-aminolevulinic acid (5-ALA) was incorporated within these nanofibers, where it remained chemically stable. In all cases, nanofiber diameters were less than 150 nm as determined by scanning and transmission electron microscopy, and encapsulation efficiency of 5-ALA was 97 ± 1% as measured by high-performance liquid chromatography. Both polymeric matrices showed rapid release kinetics in vertical cells (Franz cells) and followed Higuchi kinetics. In addition, no toxicity of nanofibers, in the absence of light, was found in HaCaT and SW480 cell lines. Finally, it was shown that loaded 5-ALA was functional, as it was internalized by cells in nanofiber-treated cultures and served as a substrate for the generation of protoporphyrin IX, suggesting these pharmaceutical vehicles are suitable for photodynamic therapy applications.